Pengaruh Kompetensi dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Perusahaan Daerah Air Minum (PDAM) Kabupaten Gowa - Hatidja, St; Jamaluddin; Artiyany, Megawati (Fakultas Ekonomi Universitas KristenTentena, 2024)
The purpose of this study was to determine the effect of competence and work environment on employee performance at the Regional Drinking Water Company (PDAM) Tirta je'neberang, Gowa Regency. The types of data used in this research are qualitative and quantitative data. Sources of data used in this study are secondary data and primary data. The analytical method used is descriptive analysis, multiple linear regression, and (T test, and F test, coefficient of determination) Y=4.376+0.639+0.1552. The results of the analysis of the correlation coefficient on the variable (X1) to (Y) of 0.951 which indicates the relationship which is strong while the variable X2 to Y is 0.980. The coefficient of determination is 97% then through the calculated f test of 640.186 > f table of 3.25 then through the t-test on the X1 variable to the Y variable at 3.775 > 1.687 while the X2 variable against the Y variable 9.449 > 1.687 so that Ha is accepted and Ho is rejected. Thus the hypothesis which states that competence and work environment partially and simultaneously have a significant effect on employee performance at the Regional Air Mining Company (PDAM) Tirta je'neberang, Gowa Regency.